Inovasi Pembuatan Kue Keranjang Dengan Penambahan Puree Umbi Bit (Beta Vulgaris L.) Dan Variasi Isian Kismis Sebagai Obyek Usaha - Diandari Ridhaningrat; Lilis Sulandari; Any Sutiadiningsih; Ita Fatkhur Romadhoni (Pusat Riset dan Inovasi Nasional, 2023)
Kue keranjang or commonly called Nian Gao is a seasonal cake during Chinese New Year celebrations. Kue Keranjang is a typical Chinese New Year food, its color is brown, made from glutinous rice flour, water and sugar, and has a chewy and sticky texture. This study aims to determine the organoleptic properties of kue keranjang with the addition of beetroot puree and various raisin fillings including color, flavor, texture, taste, overall product preference level, chemical properties, and production raw material costs so that it can be an alternative business object.This research is a descriptive research. The amount of addition of beetroot puree is 100 grams, and 25 grams of raisins which are formed into 2 layers. Layer 1 added beetroot puree and Layer 2 added raisin filling variations. The data collection method used the observation method through organoleptic tests with a total of 30 panelists and chemical properties tests included protein, carbohydrates, fat, ash, fiber, anthocyanins and antioxidants. Organoleptic test data which includes color, flavor, taste, texture, overall preference level of the product were analyzed using quantitative descriptive with percentage.The results of research on kue keranjang with the addition of beetroot puree and various raisin fillings showed 1) Organoleptic properties of dark red color, it has distinctive flavor of kue keranjang, raisin flavor and no beetroot flavor, sweet, savory taste, raisin taste, and no beetroot taste. The texture is chewy, not mushy, and has a raisin taste and level of preference with liking criteria, 2) Chemical properties per 100 gr show carbohydrates 48.05%, protein 11.60%, fat 9.86%, moisture content 29.10%, ash 1.38%, fiber 1.40%, anthocyanins 21.88 mg, and antioxidants 86.50 mg, 3) The cost of raw materials is known to be IDR 26,900/100 gr.